INTER-COUNTRY EFFICIENCY EVALUATION IN INNOVATION ACTIVITY ON THE BASIS OF METHOD FOR DATA ENVELOPMENT ANALYSIS AMONG COUNTRIES WITH DEVELOPED AND DEVELOPING ECONOMY, INCLUDING THE REPUBLIC OF BELARUS - I. V. Zhukovski; A. B. Gedranovich (Наука и техника)
The paper considers a problem on efficiency evaluation of innovation activity in 63 countries with developed and developing economies while using a method for data envelopment analysis. The following results of innovation activity have been used for calculation of an efficiency factor: export of high-technology products as percentage of industrial product export, export of ICT services as percentage of services export and payments obtained due to realization of intellectual property rights (in US dollars). A model of the data envelopment analysis with a changeable scale-dependent effect and which is directed on maximization of the obtained results (output-oriented VRS model) has been used for the analysis. The evaluation has shown that such countries as the USA, Israel, Sweden and some others have maximum efficiency of resource transformation into innovative activity output. The executed analysis has revealed that the Republic of Belarus has a potential for improvement of indices on innovation results.